Robotic endocrine surgery - Karabulut, Koray; Berber, Eren (Turkish Surgical Assoc, 2011)
With the refinement of the technology, easier set up, better image quality, and smaller robotic systems, there has been an interest in using the robot for more general surgical laparoscopic procedures as well as for endocrine surgery. Endocrine surgery procedures are excellent targets for robotic instrumentation when compared with the conventional endoscopic techniques, since it requires to work in a small space, significantly limiting the type of equipment that can be used. In spite of its deficiencies and unanswered questions especially about cost effectiveness, robotic technology seems to overcome the limitations of conventional laparoscopic technology in endocrine surgery. The techniques in robotic transaxillary thyroidectomy, parathyroidectomy and both lateral transabdominal and posterior retroperitoneal adrenalectomies are described and the literature regarding the periprocedural outcomes of this new technology in endocrine surgery is reviewed in this article.
Robotik endokrin cerrahi
Keywords: Endocrine surgery; robotic surgery